MOS1 functions closely with TCP transcription factors to modulate immunity and cell cycle in Arabidopsis. (30th November 2017) - Zhang, Ning; Wang, Zhixue; Bao, Zhilong; Yang, Leiyun; Wu, Dianxing; Shu, Xiaoli; Hua, Jian
Summary: Emerging evidence indicates a close connection between cell‐cycle progression and the plant immune responses. In Arabidopsis, MODIFIER OF snc1‐1 ( MOS1 ) modulates a number of processes including endoreduplication and plant disease resistance, but the molecular mechanism underlying this modulation was not fully understood. Here, we provide biochemical and genetic evidence that TEOSINTE BRANCHED 1, CYCLOIDEA, PCF1 (TCP) transcription factors TCP15 and its homologues are mediators of MOS1 function in the immune response and are likely to be also involved in cell‐cycle control. MOS1 and TCP proteins have a direct physical interaction. They both bind to the promoter of the immune receptor gene SUPRESSOR OF npr1‐1, CONSTITUTIVE 1 ( SNC1 ) and modulate its expression and consequently immune responses. MOS1 and TCP15 both affect the expression of cell‐cycle genes D‐type CYCLIN 3 ; 1 ( CYCD3 ; 1 ), which may mediate the MOS1 function in cell‐cycle modulation. In addition, CYCD3 ; 1 overexpression upregulates immune responses, and SNC1 expression. This study investigated and revealed a role for MOS1 in transcriptional regulation through TCP15 and its homologues. This finding suggests the coordination of cell‐cycle progression and plant immune responses at multiple levels. Significance Statement: This study reveals that MOS1, a modulator of multiple processes, interacts with TCP transcription factors to directly regulate expression of plant immune receptor gene SNC1 to impact plant immunity. Its impact on cell cycle is also likely through TCP factors, suggesting a coordination of cell cycle progression and plant immune responses at multiple levels.